Dietary PUFA Increase Apoptosis in Stomach of Patients with Dyspeptic Symptoms and Infected with H. pylori. Issue 6 (10th May 2017) - Sharifi, Rasoul; Nouri, Mohammad; Eidi, Akram; Noormohammadi, Zahra; Dolatkhah, Homayun; Shirmohammadi, Masoud
Abstract: Drug‐resistant strains of Helicobacter pylori and poor treatment response are the main reasons for the failure in eradicating it in patients. Polyunsaturated fatty acids (PUFA) have an inhibitory effect on bacterial growth. The aim of this study was to investigate the effect of PUFA in combination with standard triple therapy on apoptosis in H. pylori infected subjects with dyspeptic symptoms. This study was a double‐blind clinical trial in which 34 H. pylori infected subjects with dyspeptic symptoms were randomly divided into two groups of 17 patients. The control group received standard triple therapy (amoxicillin, clarithromycin and omeprazole) and the experimental group received the standard therapy and PUFA for two weeks. Gene expression levels of caspase‐3, BCL‐2 and Bad proteins were studied with real‐time PCR, while protein levels were quantified in frozen sections and using immunohistochemistry. Compared with the control group, a significant increase ( p < 0.01) was observed in the expression of caspase‐3 and Bad genes and a significant reduction ( p < 0.05) in the expression of Bcl‐2 gene. The protein level of active caspase‐3 and Bad protein was significantly increased and the level of Bcl‐2 protein was significantly decreased ( p < 0.05). The results of this study show that oral administration of PUFA in combination with the standard triple therapy increased apoptosis in H. pylori ‐infected patients with dyspeptic symptoms. This increase in apoptosis may partly reduce drug resistance in these patients. Our results suggest inclusion of a dietary PUFA containing fatty acid supplement may improve treatment of patients that are refractory to the standard triple therapy.